The golden book of Rammohun Roy - Rammohun Roy, Raja; Mitra, Sarojamohana; Rammohun Library & Free Reading Room (Calcutta : : Rammohun Library & Free Reading Room, 1997)
Comprises articles, reminiscences, etc. on Raja Rammohun Roy, 1772?-1833, socioreligious reformer and pioneer in the reawakening of modern India; most reprinted from the commemoration volume of 1933.
"On the occasion of the 225th Birth Anniversary of Raja Rammohun Roy"--T.p. verso.
"A list of the principal publications and other writings of Raja Rammohun Roy": p. 562-574
Keywords: Rammohun Roy, -- Raja, -- 1772?-1833; Statesmen -- India -- Biography; Social reformers -- India -- Biography